2002
DOI: 10.1097/00000658-200202000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic Appearance of Nonpalpable Breast Cancer Reflects Pathologic Characteristics

Abstract: ObjectiveTo study the relationship of mammographic appearance of nonpalpable breast cancer to the pathologic characteristics. Summary Background DataThe mammographic appearance of nonpalpable breast cancer may be associated with pathologic variables having prognostic significance, which could influence clinical management. MethodsThe authors correlated the mammographic appearance and pathologic characteristics of 543 nonpalpable malignancies diagnosed in a single institution between July 1993 and July 1999. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(81 citation statements)
references
References 24 publications
(28 reference statements)
7
69
1
4
Order By: Relevance
“…To our knowledge, there have been several studies on the association between mammographic features and the prognostic or pathological characteristics of breast cancer [22][23][24][25]27], but only two studies have been published on the association between sonographic features and the histological grade of invasive breast cancer [21,26]. As far as we know, no report has been published on the association between the mammographic and sonographic features analysed according to the BI-RADS lexicon and the pathological characteristics of node-negative invasive breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, there have been several studies on the association between mammographic features and the prognostic or pathological characteristics of breast cancer [22][23][24][25]27], but only two studies have been published on the association between sonographic features and the histological grade of invasive breast cancer [21,26]. As far as we know, no report has been published on the association between the mammographic and sonographic features analysed according to the BI-RADS lexicon and the pathological characteristics of node-negative invasive breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Gajdos et al [23] carried out a study of 543 nonpalpable breast cancers, and demonstrated that lymphatic invasion was more common in cancers presenting as a mass with calcifications. In our study, mammographic types that were significantly associated with LVI were spiculated or non-spiculated masses with calcifications.…”
Section: Correlation Between Imaging and Prognostic Factors In Breastmentioning
confidence: 99%
See 2 more Smart Citations
“…Grouped microcalcifications in mammograms (MG) and digital tomosynthesis of the breast (DBT) are the best signs of a potentially underlying DCIS or an invasive cancer. Further examinations like a core needle biopsy or vacuumassisted biopsy are needed for clarification or exclusion of malignancy [6]. However in up to 40% (mostly in low grade DCIS) no calcifications can be seen [7].…”
Section: Introductionmentioning
confidence: 99%